(untitled) (Journal of Fatima Jinnah Medical University, 2018)
ABSTRACT Objectives: To determine the insulin resistance in diabetic type 2 males and females in the fasting state in the population of Lahore, Pakistan. Methods: The study group comprised of 122 individuals (49 males and 73 females), who were > 30 years old. Parameters, serum glucose and serum insulin levels were estimated in fasting state and based on those, the insulin resistance indices (IRI) was calculated by HOMA-IR 1 in the total sample population, in males and in females separately. Results: The study group had increased average levels of serum glucose (10.008 + 0.326 mmol/L) and insulin resistance indices (5.370 + 0.396) when compared with the normal adult population. There was no difference based on gender. IRI was significantly different based on groups of W/ht in males. On the other hand, the correlations of all the clinical parameters with their respective serum glucose, serum insulin and IRI were strongly positive (r > 0.8) and highly significant (p value < 0.001) irrespective of gender status and parameter type. Conclusion: The results for anova could mean that the fat distribution only in males is responsible for metabolic derangements; though the results for correlation show no discrimination based on gender.